Victory through organization why the war for talent is failing your company and what you can do about it - Ulrich, David 1953-; Kryscynski, David; Brockbank, Wayne; Ulrich, Mike (McGraw-Hill, 2017)
Filled with fact-based insights and field-tested strategies; this book demonstrates that organizational success isnt just about the talent you haveits about how the collective organization makes the individual talent better. --
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Personnel management; Human capital -- Management; Personnel Management; Personnel; Direction; Human capital; Management